Science Training for Journalists: An Essential Tool in the Post-Specialist Era of Journalism - Menezes, Sunshine (Frontiers in Communication, 2018)
A majority of U.S. adults are concerned about a rise in misinformation regarding current issues and events. The spread of inaccurate information via social media and other sources has coincided with a massive transition in the news industry. Smaller newsrooms now have fewer journalists and their responsibilities have shifted toward producing more stories, more quickly, while contributing to their outlets’ blogs and social media feeds. Lean newsroom budgets also eliminated in-house professional development for journalists, making external training programs an essential vehicle for reporters and editors to gain new content knowledge, sources, and skills in a constantly evolving news landscape. The loss of specialized beat reporters in many newsrooms since the mid-2000s has made training especially critical for journalists covering complex, science-based topics like climate change and public health. In the U.S., relatively few organizations offer science training opportunities for journalists, but the need and demand for these programs is growing as newsrooms increasingly rely on generalist reporters to cover a wide range of scientific topics. This perspective summarizes the challenges non-specialist reporters face in covering science-based stories and describes a successful training model for improving science and environmental news coverage to yield reporting that is not only accurate, but also offers the nuance and context that characterizes meaningful journalism.